CD24 expression does not affect dopamine neuronal survival in a mouse model of Parkinson's disease - Stott, Simon R. W.; Sleeman, Jonathan P. (PLOS ONE, 2017)
Parkinson’s disease (PD) is a progressive neurodegenerative condition that is characterised by the loss of specific populations of neurons in the brain. The mechanisms underlying this selective cell death are unknown but by using laser capture microdissection, the glycoprotein, CD24 has been identified as a potential marker of the populations of cells that are affected in PD. Using in situ hybridization and immunohistochemistry on sections of mouse brain, we confirmed that CD24 is robustly expressed by many of these subsets of cells. To determine if CD24 may have a functional role in PD, we modelled the dopamine cell loss of PD in Cd24 mutant mice using striatal delivery of the neurotoxin 6-OHDA. We found that Cd24 mutant mice have an anatomically normal dopamine system and that this glycoprotein does not modulate the lesion effects of 6-OHDA delivered into the striatum. We then undertook in situ hybridization studies on sections of human brain and found—as in the mouse brain—that CD24 is expressed by many of the subsets of the cells that are vulnerable in PD, but not those of the midbrain dopamine system. Finally, we sought to determine if CD24 is required for the neuroprotective effect of Glial cell-derived neurotrophic factor (GDNF) on the dopaminergic nigrostriatal pathway. Our results indicate that in the absence of CD24, there is a reduction in the protective effects of GDNF on the dopaminergic fibres in the striatum, but no difference in the survival of the cell bodies in the midbrain. While we found no obvious role for CD24 in the normal development and maintenance of the dopaminergic nigrostriatal system in mice, it may have a role in mediating the neuroprotective aspects of GDNF in this system.
Gesehen am 27.08.2020